2021
DOI: 10.1111/jcms.13201
|View full text |Cite
|
Sign up to set email alerts
|

The Trade Effects of the Economic Partnership Agreements between the European Union and the African, Caribbean and Pacific Group of States: Early Empirical Insights from Panel Data*

Abstract: Provisionally applied EPAs at a glance 2.1 EU-CARIFORUM EPA 2.2 EU-Pacific EPA 2.3 EU-ESA EPA 2.4 EU-Cameroon EPA 2.5 EPAs with West Africa 2.6 EU-SADC EPA 3 Empirical model 3.1 Data 3.2 Estimation strategy 4 Estimation results 4.1 Total trade 4.2 Agricultural trade 4.3 Manufactures trade 5 Conclusion and outlook References Appendix The trade effects of the EPAs between the EU and the ACP countries: early empirical insights from panel data German Development Institute / Deutsches Institut für Entwicklungspolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, Su and Zhou [21] showed that the economy-of-scale of ASEAN countries significantly affects China's export structure and that a free trade agreement (FTA) always has a stronger impact on the creation of new trade than it does on the diversification of existing trade [70]. As a result, the volume of trade will increase under an FTA [74,75]. The competitiveness of traded products has increased due to deepening economic globalization and inter-country dependence.…”
Section: Hypothesis 3 (H3) Cultural Distance Negatively Affects Agric...mentioning
confidence: 99%
“…In addition, Su and Zhou [21] showed that the economy-of-scale of ASEAN countries significantly affects China's export structure and that a free trade agreement (FTA) always has a stronger impact on the creation of new trade than it does on the diversification of existing trade [70]. As a result, the volume of trade will increase under an FTA [74,75]. The competitiveness of traded products has increased due to deepening economic globalization and inter-country dependence.…”
Section: Hypothesis 3 (H3) Cultural Distance Negatively Affects Agric...mentioning
confidence: 99%
“…Stender et al (2021);Plaisir et al (2021);Fuenfzig et al (2021). 14 These findings are also supported byCirera et al (2016) …”
mentioning
confidence: 99%